‘Abd al-Majīd al-Najjār’s Perspective on Maqāṣid al-Sharī’ah - Faishal Agil Al Munawar (JURIS (Jurnal Ilmiah Syariah), 2021)
Maqāṣid Al-Sharī’ah is a discipline that gives enlightenment on understanding and development of Islamic law. Moreover, it can also be used as a verdict (Istinbāṭ) for a Mujtahid. This particular research discusses ‘Abd Al-Majīd Al-Najjār and his unique perspective on Maqāṣid Al-Sharī’ah. The research encompasses library research category with descriptive qualitative approach to point out and reveal Abdul Majid An-Najjar’s Maqāṣid Al-Sharī’ah views. The result displays Majority of Maqāṣid Al-Sharī’ah experts (Maqāṣidiyyūn), the core of Maqāṣid Al-Sharī’ah is to manifest Al-Ḍarūriyyāt Al-Khams (five substances), but ‘Abd Al-Majīd Al-Najjār has different notion which is Maqāṣid Al-Sharī’ah ‘Alā Dawāir Al-Ḥayāh Al-Insāniyyah (human life Maqashid Al- Sharī’ah) that realizes Al-Ḍarūriyyāt Al-Thamān (eight substances) that contains Ḥifẓ Al-Dīn (preserving religion), Ḥifẓ Insāniyyah Al-Insān (preserving humanity), Ḥifẓ Al-Nafs Al-Insāniyyah (protecting soul), Ḥifẓ Al-‘Aql (preserving mind), Ḥifẓ Al-Nasl (preserving heirs), Ḥifẓ Al-Kiyān Al-Ijtimā’ī (preserves social behavior), Ḥifẓ Al-Māl (taking care of property) and Ḥifẓ Al-Bīah (preserving environment) with noble purposes to gain benefits and salvation for here and hereafter. According to ‘Abd Al-Majīd Al-Najjār, realizing benefits for mankind by materializing merits and avoiding perilous things here and hereafter are the supreme objective of Islamic Sharī’ah.